Upaya Peningkatan Hasil Belajar Matematika Materi Perkalian melalui Pendidikan Matematika Realistik Siswa Kelas III SD Negeri Karanglo - Azizah, Amalia Nurul (PANCAR, 2018)
The purpose of this study was to improve the learning outcomes of mathematics in the multiplication of third grade students in the first semester of Karanglo Elementary School in Cilongok District, Banyumas District 2017/2018 Academic Year. This research is a Class Action Research conducted in two cycles. The cycle begins with planning, action, observation and reflection. The research subjects were teachers and third grade students of Karanglo Elementary School in the academic year 2017/2018. Data collection techniques used were tests, observations, interviews and documentation. Based on data from the results of the research that has been carried out an increase in the value of the final test in each cycle. This can be seen from the percentage of students who get a score of ? 65 (KKM). In the pre cycle the number of students who completed 37%, in the first cycle became 63% or increased by 26%, and the first cycle to the second cycle by 85% or up by 22%. By looking at the percentage in the second cycle, an indicator of the number of students who get a score of ? 65 at least 80% has been achieved.